Building the gymnastic body: The science of gymnastic strength training - Sommer, C. (Olympic Bodies, LLC, 2008)
The world has always marveled at their amazing physiques whenever the gymnasts take center stage at the world`s premier athletic competitions. Awe-inspiring feats of strength, skill and agility are performed with what appears to be effortless ease. The gymnasts seem a breed apart and their physical accomplishments appear to be beyond the reach of the average man; that is until now. For the first time, Building the Gymnastic Body allows you to go deep within the world of gymnastics strength training. Extremely comprehensive and detailed, with nearly 200 exercises (many of which have never been seen before by the general public) and well over 500 photographs, it is a complete developmental template for building the essential foundation of strength required for all gymnastics success. Whether you are a competitive athlete looking for an edge, a fitness enthusiast or just beginning a healthier lifestyle, Building the Gymnastic Body is the answer you have been searching for. TABLE OF CONTENTS INTRODUCTION - I CHAPTER ONE - Gymnastics as Conditioning CHAPTER TWO - General Information, Tools of the Trade - 9, Basic Gymnastics Terminology - 11, The Selection of These Exercises - 15, Handstands & Press Handstands - 16 CHAPTER THREE - Basic Strength - 21 CHAPTER FOUR - Fundamental Static Positions; L-sit - 26, Straddle L - 30, Manna - 35, Back Lever - 41, Front Lever, Planche - 49 CHAPTER FIVE - Upper Body Pressing; Fundamental Bodyweight Exercises, Push-up Variations - 61, Dip Variations - 68, HSPU Variations - 76, Multi-plane Pressing Variations - 83 CHAPTER SIX - Upper Body Pulling; Row Variations - 91, Pull-up Variations - 96, Curl Variations - 103, Multi-plane Pulling Variations - 106 CHAPTER SEVEN - Combined Pull/Press; Muscle-up Variations - 113, Other CPP Variations - 118 CHAPTER EIGHT - Core; V-up Variations - 123, HLL Variations - 127, Lower Back Variations - 132, Oblique Variations - 138, Straight Body Variations - 144 CHAPTER NINE - Legs; Deck Squat Variations - 156, Single Leg Squat Variations - 159, Hamstring Variations - 165 CHAPTER TEN - Program Design Options; Static Strength Training - 171, Basic Strength Training - 175, Integrated Training - 178, Managing Intensity - 179, Group Training - 182 APPENDIX A - Tips for Increasing Pull-ups - 185 APPENDIX B - Static Strength Only Training Results - 186 APPENDIX C - 120 Muscle-ups in 15 minutes - 187 Index